Study of Single Phase Mass Transfer between Matrix and Fracture in Tight Oil Reservoirs - Renyi Cao; Zhongyi Xu; Linsong Cheng; Yuanyuan Peng; Yang Wang; Zhuoliang Guo (Geofluids)
In tight fractured reservoirs, oil in matrices is mainly explored due to mass transfer mechanisms during the pressure depletion process. In the modeling of mass transfer in fractured reservoirs using the dual porosity concept, the shape factor is the most important parameter and should be described accurately. However, the current shape factors are not suited for tight oil reservoir simulation because the characteristics of tight oil reservoirs are not taken into account. In order to solve this problem, a new mass transfer function for tight fractured oil reservoirs is proposed by introducing a new time-related correction factor which could consider not only the existence of the boundary layer in nano-microscale throats in tight porous media but also the heterogeneous pressure distribution in matrix blocks. In addition, special contact relations between matrix and fracture are included. The correction factor presented in this study is verified using the experimental data and numerical simulation results. Data analysis results demonstrate that the lower and slower the pressure propagation velocity, the longer the duration time of unsteady flow compared to conventional reservoirs. Therefore, in the calculation of mass transfer flow in tight oil reservoirs, the unsteady flow between fracture and matrix cannot be ignored.